The Importance of Training in a Japanese MNC : Workers' Perspectives - Norasemas, Mat Nor (2003)
This study was conducted on a small Japanese multinational company (MNC) located in Perlis, in northern Malaysia. It investigates the importance of training from the workers’ point of view. Japanese MNCs are noted for their heavy focus on on-the-job training (OJT) especially in Japan. This study aims to determine the relationships between five independent variables (worker orientation process, job performance, self-development, knowledge and skill and technological advances) and the importance of training accorded by the employees. 71 employees responded to the distributed questionnaires. It was found that the Japanese firm had practiced both the off-job-training and also the on-the-job training for its employees. From the workers’ perspectives, they said the five factors did not influence their perceptions so much on the importance of training that they had received. However, job performance seems to have a bit more impact on their perceptions about how they view training compared to the other four factors. They just followed their employer’s instruction to attend any training because to them, training was part of their job. Generally they did not understand the goals and benefits of the training that they had received.